2001
DOI: 10.1159/000053855
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Infiltration and Degranulation in Normal Human Tissues: Evidence for Eosinophil Degranulation in Normal Gastrointestinal Tract

Abstract: Eosinophils play an important role in the pathogenesis of inflammatory diseases such as bronchial asthma and host immunity to parasitic infections. Deposition of eosinophil granule proteins and concomitant tissue damage have been documented in various diseases. Here, we review and summarize results of our immunofluorescence studies of eosinophil infiltration and degranulation in various normal human tissues. Furthermore, because eosinophil infiltration and degranulation are not normally present in healthy tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Therefore, the chemokines up-regulated by VacA stimulation may contribute to the infiltration of inflammatory cells to mucosa infected with VacA-producing H. pylori. In addition, VacA-stimulated eosinophils may be an important factor in triggering tissue damage, since eosinophils can induce H. pylori-related tissue damage through degranulation processes (19,39 (47). Heterodimers of p65 and p50 are the predominant NF-B complexes that translocate to the nucleus after H. pylori infection of intestinal epithelial cells (20,23).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the chemokines up-regulated by VacA stimulation may contribute to the infiltration of inflammatory cells to mucosa infected with VacA-producing H. pylori. In addition, VacA-stimulated eosinophils may be an important factor in triggering tissue damage, since eosinophils can induce H. pylori-related tissue damage through degranulation processes (19,39 (47). Heterodimers of p65 and p50 are the predominant NF-B complexes that translocate to the nucleus after H. pylori infection of intestinal epithelial cells (20,23).…”
Section: Discussionmentioning
confidence: 99%
“…In the other groups eosinophils were located predominantly in the upper half of the lamina propria (B, IBS; C, allergy) and, less frequently, distributed equally (D, others); however, they were in general unaccompanied by an increase in overall cellularity of the lamina propria. Eosinophil infiltration and degranulation occur in many diseased tissues; in normal tissue studies, only the gut showed striking eosinophil infiltration and degranulation (18). Although they are normal constituents of the mucosa of the gastrointestinal tract, there has been no definitive determination of the number of eosinophils that can be defined as "normal."…”
Section: Discussionmentioning
confidence: 99%
“…One of the novelties of the current paper lies in the fact that it provides a morphologic correlate of the biochemical findings, and allows a visual window into the mechanism involved. It is likely that eosinophil degranulation contributes to clinical symptoms, perhaps by inducing inflammation and fibrosis [3]. Although our patients who were clinically well still had some degree of free-lying esophageal granules, the significant decrease in granule number suggests that the lesser degree of degranulation is the factor leading to the clinical improvement.…”
Section: Discussionmentioning
confidence: 62%
“…Free-lying granules serve as a surrogate marker for released eosinophil products that promote tissue damage, inflammation, remodeling, and fibrosis [3]. Eotaxin-3 is a chemokine stimulated by T-helper cytokines to recruit and activate eosinophils.…”
Section: Introductionmentioning
confidence: 99%